Reports of deaf students on the Special School - doi: 10.4025/actascieduc.v34i1.15079 - Balan, André Luis (2012)
This excerpt (adapted) presents an analysis of interviews performed with three (3) deaf students about their perceptions and educational experiences in the context of educational institutions and special education. Through this study it is confirmed that students are aware of some difficulties of special schools, besides feeling prejudiced because of these flaws. The analysis of the interviews about some perceptions of deaf students on their educational experiences in special schools allowed identifying, through their reports, recurring events within the special school, which nfluence or even limit the quality of education for these students.